Asymptotic behavior of solutions of sum-difference equations - Adiguzel, H.; Can, E. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
In this study, we present an investigation of the asymptotic behavior of solutions of sum-difference equations. Based on some mathematical inequalities, we have obtained our results. The obtained results can apply to some fractional type difference equations as well.
Айырымдардың қосындысы теңдеулерінің шешімдерінің асимптотикасы
Асимптотика решений уравнений суммы разностей
Keywords: asymptotic behavior; oscillation; nonoscillation; difference equation; Caputo fractional difference operator